Fatal Hemoptysis Secondary to Severe Pulmonary Veins Stenosis and Fibrosing Mediastinitis following Radiofrequency Ablation for Atrial Fibrillation: A Case Report and Review of the Literature - Vladut Mirel Burduloi; Flavia Catalina Corciova; Gabriela Dumachita Sargu; Raluca Ozana Chistol; Alexandra Cristina Rusu; Cristinel Ionel Stan (Reports, 2023)
Fatal hemoptysis secondary to severe pulmonary veins stenosis and fibrosing mediastinitis is an exceptional late complication of radiofrequency ablation for atrial fibrillation. We report the case of a 53-year-old male with a history of atrial fibrillation treated by radiofrequency ablation and admitted in our center 6 months after the procedure because of aggravating dyspnea and fatigability. Transthoracic echocardiography showed moderate dilation of right heart cavities, severe pulmonary hypertension and a turbulent flow in superior pulmonary veins. The cardiologist suspected pulmonary vein(s) stenosis and so cardiac computed tomography (CT) angiography was performed, with findings of severe stenosis of the right superior, right inferior and left inferior pulmonary veins, near-occlusion of the left superior pulmonary vein and the vein draining the apical segment of the right lower lobe. The CT scan also revealed soft tissue attenuation of the mediastinum posterior to the left atrium suggesting fibrosing mediastinitis together with parenchymal findings consistent with pulmonary veno-oclusive disease and an area of hemorrhagic infarction. Fatal hemoptysis occurred 3 days later, before treatment was attempted. In conclusion, severe pulmonary vein stenosis and fibrosing mediastinitis are rare but devastating complications of radiofrequency ablation. Prevention and early diagnosis are the key elements as these entities are potentially life-threatening.